Features of the coordination skills of school children of senior grades who do judo - Shmelov, Stanislav (ScienceRise: Pedagogical Education, 2026)
This article examines the characteristics of the coordination abilities of judokas with varying levels of athletic proficiency when performing the Romberg test using computerised stabilography. The relevance of the study lies in the need to identify modern and innovative methods for assessing the functional condition, balance maintenance system and postural stability of senior school pupils and high-level athletes, which are key components of coordination fitness in judo. The aim of the study is to identify differences in coordination indicators between highly skilled athletes and 10th–11th-grade schoolchildren who practice judo at a beginner level. The study involved 63 male school pupils in the older age group and 14 highly skilled athletes. The computerised stabilography method was used to assess balance. The following parameters were examined: MO(x), MO(y), Q(x), Q(y), R, V, OD, LX, LY, КФР and the balance coefficient, which was demonstrated as the position of the center of pressure, the amplitude and speed of oscillations, the length of the trajectory of movement and the overall efficiency of the balance maintenance mechanisms. The article identified differences between the groups across all the specified indicators. Thus, during the experiment, highly skilled athletes demonstrated smaller variations in the amplitude of the center of pressure, lower rates of movement, and better balance maintenance compared to schoolchildren at a beginner level in judo. The results of the study indicate more effective functioning of the balance maintenance system and a higher level of coordination in skilled judo athletes. The model of stabilographic indicators developed can be used as a guideline for monitoring the functional condition of judo athletes, assessing their ability to maintain balance and coordination, and, in general, improving the teaching and training process in judo